Opportunities for using the methods of andragogy in sightseeing - Kurek, Artur (Turystyka i krajoznawstwo, 2021)
An increasing percentage of older people participating in cognitive tourism forces the organizers of such trips to adapt their way of presenting what is of tourist value. The article is an attempt to transfer experience related to adult education to the field of tourism. It is divided into four parts: the first describes andragogy and its methods, the next focuses on the model of behavior for a guide while working with adults, followed by one describing the selection methods appropriate for this group of tourists. The article ends with an epilogue that clearly indicates the need to use andragogy in preparing sightseeing.